Design and development of the network interface, packets scheduling and interference mitigation schemes for LTE based femtocell networks / Sinan Ghassan Abid Ali Al-Nasir - Abid Ali Al-Nasir, Sinan Ghassan (Institute of Graduate Studies, UiTM, 2017)
Cellular networks face numerous challenges in providing services for indoor users.Therefore, femtocells are suggested as a solution to indoor coverage issues that macro cells have failed to address to date in cellular networks such as Global System for Mobile Communication (GSM), Universal Mobile Telecommunications System (UMTS), and Long Term Evolution (LTE). Although femtocells can provide various benefits for both operators and users, many technical challenges must be resolved for effective femtocell deployment in real environments. In this thesis, the network interface, the packet scheduling and the interference management challenges are investigated in order to address these issues with proper solutions. The network interface challenge is related to the integration of the femtocell in a cellular network such as LTE. The proposed solution is to deploy an IP Multimedia Subsystem (IMS) as an integration platform between the femtocell and the LTE cellular network. Thus, an IMS module has been implemented for signalling in a LTE-based femtocell network that contains both registration and invitation procedures. Based on this study, it has been observed that the integration of an IMS in a LTE based femtocell network can improve the network performance since the Packet Loss Ratio (PLR) can be minimised…